2015
DOI: 10.1016/j.jfineco.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Do analysts matter for governance? Evidence from natural experiments

Abstract: Building on two sources of exogenous shocks to analyst coverage-broker closures and mergers, we explore the causal effects of analyst coverage on mitigating managerial expropriation of outside shareholders. We find that as a firm experiences an exogenous decrease in analyst coverage, shareholders value internal cash holdings less, its CEO receives higher excess compensation, its management is more likely to make value-destroying acquisitions, and its managers are more likely to engage in earnings management ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
327
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(349 citation statements)
references
References 87 publications
17
327
2
3
Order By: Relevance
“…The recent paper by Chen, Harford, and Lin (2015) shows a positive monitoring role of analysts: following a decrease in coverage shareholders value internal cash holdings less, their CEOs receive higher excess compensation, and they are more likely to engage in value-destroying acquisitions.…”
Section: Relation To the Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The recent paper by Chen, Harford, and Lin (2015) shows a positive monitoring role of analysts: following a decrease in coverage shareholders value internal cash holdings less, their CEOs receive higher excess compensation, and they are more likely to engage in value-destroying acquisitions.…”
Section: Relation To the Existing Literaturementioning
confidence: 99%
“…The same arguments hold for the first-stage regression of the number of analysts and CVC investments in the next section. 29 A recent paper by Chen, Harford, and Lin (2015) shows that firms that experience an exogenous decrease in analyst coverage are more likely to make value-destroying acquisitions. Their result suggests that financial analysts play a governance role that leads managers to acquire better targets.…”
Section: Number Of Analysts and Acquisitionsmentioning
confidence: 99%
“…Karpoff et al (2010) [4], Hirshleifer et al (2011) [5] found that short selling can restrain the financial fraud. Chen et al (2015) [12], Fang et al (2016) [13] found that short selling can restrain earnings management and improve the reliability of financial information. Li (2017) [14] found that the introduction of short selling significantly improved the quality of the target company's information disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lang & Lundholm, 1996;Lang et al, 2004). Outros estudos também destacam o impacto do acompanhamento de analistas no custo de capital e no ambiente corporativo das empresas (Chen et al, 2014;Cheng & Subramanyam, 2008;Easley & O'hara, 2004). Relacionar se o acompanhamento de analistas e o ambiente informacional é impactado pela diretoria executiva da empresa é trazido por Jiraporn et al (2012) de modo único na literatura e contribui para um melhor entendimento entre a influência das ações dos CEOs e seus impactos que permeiam todo ambiente corporativo, inclusive a cobertura de analistas financeiros.…”
Section: Justificativaunclassified
“…O papel dos analistas financeiros como monitores dos executivos é analisado por Chen et al (2014). Através de um experimento natural 7 , foi verificado que a redução do nú-mero de analistas financeiros resulta em uma perda do valor das reservas direcionadas ao acionista, e a um aumento de salários dos executivos.…”
Section: Analistas Financeirosunclassified